Pengaruh Konsumsi, Produksi Dalam Negeri, Inflasi, dan Kurs USD Terhadap Volume Impor Beras Indonesia - I Made Dwityam Suyanca; Anak Agung Ketut Ayuningsasi (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
The rapid growth of globalization has led to an increased demand for food. This study aims to: 1) examine the simultaneous impact of consumption, domestic production, inflation, and the USD exchange rate on Indonesia's rice import volume, and 2) assess the individual effects of these factors on rice import volume. A quantitative associative approach is employed in this research. The study utilizes secondary data, collected through a non-participant observation method. The findings indicate that consumption, domestic production, inflation, and the USD exchange rate collectively influence Indonesia's rice import volume. Partially, consumption and inflation have a positive impact, while domestic production and the USD exchange rate have a negative impact on rice imports.